Exploring Nurses' Decision‐Making Through the Lens of Capability: A Framework for Understanding Autonomy in Complex Care Environments - Lavoie, Patrick (Journal of advanced nursing, 2025)
To apply the capability approach to understand ICU nurses' decision-making autonomy. A qualitative study using Amartya Sen's capability approach as a conceptual framework. This study reanalyzed qualitative data from a previous investigation involving semi-structured interviews with 39 experienced Canadian ICU nurses who described their decision-making processes in managing post-cardiac surgery bleeding. The analysis examined how resources (e.g., information, therapeutic and human), conversion factors (personal, social and institutional) and professional agency interact to shape nurses' decision-making capabilities. Nurses' decision-making capabilities encompass: (1) obtaining necessary information, (2) interpreting information to make judgements and (3) making actionable decisions. These capabilities enable nurses to achieve valued outcomes such as clinical effectiveness, patient and family comfort, professional growth and personal fulfilment. However, they are shaped not only by clinical expertise or competency but also by structural and contextual factors, including resource constraints, institutional policies, interprofessional dynamics and hierarchical relationships. These factors influence nurses' autonomy and real opportunities to translate clinical judgements into action. The capability approach offers a reflective lens for examining the contextual conditions that shape nurses' autonomy. By shifting the focus beyond individual competence, it highlights the broader structural and relational influences on nurses' ability to make and implement clinical decisions. Understanding decision-making as a capability underscores the importance of creating supportive environments where nurses can apply their expertise. The findings call for context-sensitive strategies in education, policy and practice that valorise nurse agency and respond to the systemic factors influencing decision-making in critical care settings. What problem did the study address? This study examined the gap between nurses' clinical expertise and the ability to act on decisions in practice, exploring how contextual factors influence their autonomy in critical care settings. What were the main findings? Decision-making autonomy is shaped by the interaction of individual, organisational and systemic factors-including access to resources, team dynamics and institutional norms-underscoring the need for context-sensitive strategies to support nurses' decision-making. Where and on whom will the research have an impact? These findings can inform educators, policymakers and healthcare leaders seeking to strengthen decision-making, education and support, especially in complex or resource-constrained environments. This report adheres to the Standards for Reporting Qualitative Research. This study did not include patient or public involvement in its design, conduct, or reporting.